2006
DOI: 10.1016/j.cub.2006.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Mediated by the TRPM8 Cold Receptor in Chronic Neuropathic Pain

Abstract: TRPM8 and its central downstream mediators, as elements of endogenous-cooling-induced analgesia, represent a novel analgesic axis that can be exploited in chronic sensitized pain states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
326
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(358 citation statements)
references
References 61 publications
12
326
1
Order By: Relevance
“…Although TRPM8 is restricted to a small subset of sensory neurons, it is critical in most aspects of cold sensation (Bautista et al, 2007;Colburn et al, 2007;Dhaka et al, 2007). Even more notable, the channel is key in the analgesia provided by moderate cooling and modest doses of cooling compounds (Proudfoot et al, 2006;Dhaka et al, 2007). Thus, both in vitro and in vivo data suggests a single molecule, expressed on a small number of sensory axons, mediates many aspects of sensory signaling depending on the quality of the stimulus and tissue state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TRPM8 is restricted to a small subset of sensory neurons, it is critical in most aspects of cold sensation (Bautista et al, 2007;Colburn et al, 2007;Dhaka et al, 2007). Even more notable, the channel is key in the analgesia provided by moderate cooling and modest doses of cooling compounds (Proudfoot et al, 2006;Dhaka et al, 2007). Thus, both in vitro and in vivo data suggests a single molecule, expressed on a small number of sensory axons, mediates many aspects of sensory signaling depending on the quality of the stimulus and tissue state.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking TRPM8 are deficient in detecting innocuous cool temperatures and exhibit a partially defective phenotype in responding to noxious cold (Bautista et al, 2007;Colburn et al, 2007;Dhaka et al, 2007). Moreover, activation of TRPM8 is required for the analgesia provided by cooling and cooling compounds (Proudfoot et al, 2006;Dhaka et al, 2007) and, paradoxically, is essential in injuryevoked hypersensitivity to cold (Colburn et al, 2007;Dhaka et al, 2007). Thus, TRPM8 plays a principal role in the perception of cold temperatures and raises the question: how can a single receptor be involved in multiple, and in some cases antagonistic (pain vs analgesia), aspects of sensory signaling?…”
Section: Introductionmentioning
confidence: 99%
“…One equivalent of 3-(2-bromoethyl)indole (1) or intermediate 2 or 3 was dissolved in THF and 1.5 eq of the proper amine, 1.5 eq of TEA, 1.5 eq of NaI and 0.3 eq of (CH 3 COO) 2 Pd were added to this solution (Scheme I). The reaction was conducted under W, at 100°C, for 20 minutes.…”
Section: General Procedures For the Synthesis Of Derivatives 4-12mentioning
confidence: 99%
“…One of the most investigated effects produced by TRPM8 modulation is the analgesia against chronic and neuropathic pain: in fact, it has been reported that peripheral and central activation of TRPM8 induces analgesia, specifically reversing the sensitization of the behavioral reflexes elicited by peripheral nerve injury. 2 Notably, both TRPM8 agonists and antagonists exert analgesic effects: in particular, while TRPM8 agonists produce profound analgesia 2 at very low concentrations, even greater effects have been reported for TRPM8 antagonists. 3 This analgesia modulation represents a novel approach in a largely unmet therapeutic need.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that menthol induces cold and pain sensations in subjects [5]. Application of a given dose of menthol or icilin is associated with cooling perception or pain relief, whereas treatment with higher doses of menthol causes burning, *Address correspondence to this author at the Chemistry and BioScience of Science Course, Graduate School of Science & Engineering, Kagoshima University, Kagoshima, Japan; Tel: 81-99-285-8939; Fax: 81-99-285-8939; Email: kasai@sci.kagoshima-u.ac.jp irritation, and pain [5][6][7][8]. In mammals, cold perception is generally believed to be mediated by a small subpopulation of unmyelinated C and thinly myelinated A primary afferent fibers that discharge in the innocuous temperature range of 15°C -28°C.…”
Section: Introductionmentioning
confidence: 99%